Frostbite incidence is a selective term and dependable on methodology — a narrative review - Schneider, Berenike; Gorjanc, Jurij (Health Promotion & Physical Activity, 2024)
Introduction: Frostbite is freezing of the tissue that mostly affects skin but also the underlying tissues. It results from prolonged exposure to temperatures below the freezing point of water (0°C). One of the many consequences of climate change is extreme cold events, which increase the risk of frostbite in the general population, particularly among individuals who are involuntarily exposed to cold for prolonged periods of time. Although frostbite has been a known phenomenon for a long time, occurring as early as 5000 years ago, the exact incidence of frostbite is not known. This is partly due to variable internal (frostbite susceptibility, hydration status, protective garments) and external etiological factors (wind chill, precipitation, altitude), that never coincide all at the same time. Objectives: The objective was to compare the incidence rates of frostbite in the published studies that focused on frostbite incidence. Methods: Out of a total of 61 studies using the keywords “frostbite” and “incidence” on PubMed, we selected seven that dealt with frostbite incidence over 20 years. We briefly summarized and compared the results of the studies. Results: The comparison of the seven studies shows a great variability of frostbite incidence depending on the population, its size, and the method of data collection. Studies that included civilian populations have significantly lower frostbite incidence rates than studies focusing on individuals who are exposed to temperatures below 0°C for extended periods, such as mountaineers, military personnel, workers in cold storage houses or homeless people. The results highlight different incidence rates for different populations and indicate that retrospectively collected data are insufficiently comparable among studies. Frostbite incidence, expressed as the ratio of injured individuals to non-injured inhabitants, is only comparable in studies using the same methodology. Enhanced frostbite susceptibility is a confirmed fact and was generally not considered in most of the studies. Conclusions: Frostbite incidences of the included studies are insufficiently comparable to draw any conclusions on possible general frostbite incidence in a population. To enhance our ability to estimate or predict frostbite occurrences within the general population, establishing an international or national frostbite registry in high-risk countries could be helpful.